Recent Mass Spectrometric Based Methods in Quantitative N-linked Glycoproteomics - R. Rebecchi, Kathryn; L. Woodin, Carrie; Desaire, Heather (Current Proteomics, 2011)
Glycoproteomics is an emerging field focused on analysis of glycosylated proteins. Glycoproteins, especially N-linked glycoproteins, have been shown to be increasingly important in biomarker analyses and biopharmaceutical drug development. Thus, relative quantitation of glycoproteins by mass spectrometry is surfacing as a powerful tool. Examples of quantitative glycoproteomic analyses include monitoring changes in protein expression levels, glycosylation site occupancy, and site-specific glycosylation. Specific quantitative strategies can be varied; however, most glycoproteomics investigations involve a glycoprotein/glycopeptide enrichment step, which is important for separating glycoproteins/ glycopeptides from the rest of a sample matrix. Depending on the goal of the quantitative study, after enrichment, the glycans can either be deglycosylated, or released, from the protein for analysis at the peptide level or analyzed as glycopeptides. Deglycosylation is typically performed in studies involving protein expression level changes or monitoring glycosylation site occupancy; whereas quantitative glycopeptide analysis is critical for monitoring changes in glycosylation in a protein-specific or glycosylation site-specific manner. Quantitation can be performed through a label-free or labeling approach. This review focuses on contrasting the various approaches' strengths and weaknesses and providing example applications of these state-of-the-art methods.
Keywords: glycoprotein enrichment